Analisis Pengaruh Gaya Kepemimpinan, Kompensasi, dan Budaya Organisasi terhadap Loyalitas Guru SMP Swasta di Kota Batam - Kiki Sumanti; Yvonne Wangdra (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study is aimed to understand if there is a connection between leadership style, compensation and organizational culture towards the loyalty of private junior high school teachers in Batam Island. The research is a quantitative research in which author gathers information by spreading questionnaires to the private high school teachers in Batu Aji, Batam Island. This research uses multiple linear regression analysis. Through the research and the analysis, we can finally conclude that it is indeed true that there is a connection in leadership style and teacher’s loyalty. Aside from that, there are also a connections between compensation and teacher’s loyalty, organizational culture to teacher’s loyalty and a connection in the three variables to the teacher’s loyalty. The highest impact in ascending order is received from leadership style, organizational culture and at the least the compensation in where the teacher is working.